GUESTS OF SAMARKAND HAVE THE OPPORTUNITY TO SEE THE «KABA»! (Academicia Globe: Inderscience Research, 2023)
Among many historical monuments, this monument also served to bring down very important information from the distant sixties to us. At the moment, it is our priority to show the guests of our country and public attention to this divine destination as much as possible.